Developing India : an intellectual and social history, c. 1930-50 - Zachariah, Benjamin 1972- (New Delhi : Oxford University Press, 2005)
Historiography of India during 1930-50 period.
Includes bibliographical references (p. [306]-325) and index.
Keywords: India -- History -- 20th century -- Historiography